Implementation Of The Social Assistance Program For The Elderly Participants (ASLUT) In Kwala Bekala Kelurahan, Medan Johor District, Medan City - Nirwana Sari (IHSA Institute, 2021)
Successful of development in education and health benefits is very severe to the problems that arise, this is not only the quantity of the number of elderly increases, also because the lack of elderly need to be considered and protected. Conditions that occur when neglect becomes one of the important things that must be addressed. To overcome this problem, the Ministry of Social Affairs of the Republic of Indonesia established a program to assist the neglected elderly in fulfilling the needs of living through the Abandoned Social Assistance (ASLUT) program. Key informants in this study were the North Sumatra Social Service officers who worked in the field of social rehabilitation. The main informant in this research is an assistant program of ASLUT, and two elderly people who get assistance program ASLUT. Additional informants in this study is an environmental leader and a neighbor who needs assistance with the ASLUT program. Data technique with literature study, observation, and interview. The data obtained in the field then analyzed by researchers who described with a qualitative approach. The end result can be drawn from the results of these studies. The results showed that ASLUT program implementation was started from data collection, program aid, and program evaluation. Implementation of ASLUT program conducted by communication, resources, disposition, and bureaucratic structure. And based on the results of research conducted, researchers provide suggestions for ASLUT program counterparts more often. The ASLUT program, in order for the target group to understand the program, additional resources are needed for the program beneficiaries to meet their daily needs with the help. the process of determining the recipients of the program by submitting the authority to the Social Service so that it can assist ASLUT in accordance with the most important needs.